Theoretical evidence for stationary size distribution of oxide nanoparticles in dispersion strengthened steel under cascade producing irradiation - Borisenko, Alexander (Вопросы атомной науки и техники, 2019)
A model developed in this paper describes the transport of nonequilibrium (produced by irradiation) point defects across a coherent interface in a heterophase medium. In the framework of this model we derive a kinetic equation for the distribution function of spherical nanoparticles of the second phase in a solid solution, which accounts for the flow and diffusion of nanoparticles in the dimension space as well as their dissolution in atomic collision cascades. We obtain an analytical form and study the stationary solution of this equation. The result obtained fits well to experimental data [A. Certain et al. Journal of Nuclear Mate 2013) 434, 311] on distribution of Y-Ti-O nanoparticles in the oxide dispersion strengthened ferritic steel 14YWT, irradiated with nickel ions up to 100 dpa at different temperatures. We conclude that in this case irradiation affects the distribution of fine oxide nanoparticles by creating nonequilibrium point defects rather than by cascade mixing.